Examining human trafficking issue in Malaysia’s post pandemic era: preventive measures and challenges - Zarina Othman,; Nafisah Ilham Hussein,; Norhafiza Mohd Hed, (Penerbit Universiti Kebangsaan Malaysia, 2023)
Human trafficking is a serious issue that has received international attention since the 1990s and has affected security and human rights, including Malaysia. In Malaysia, this crime is increasing despite various eradication efforts carried out by the Malaysian Government in terms of policy, legislation, enforcement, care and protection, media and publicity and awareness. The Report on Human Trafficking issued by the United States (TIP) 2021 states that Malaysia has been downgraded to Level 3, which is an unsatisfactory level. Therefore, this study aims to examine the issue of human trafficking in Malaysia during the post pandemic era by focusing its analysis on challenges and preventive measures that the government can take to fill the gaps in the enforcement of government policies and legislation. This research was conducted using qualitative methods using primary sources obtained from in-depth interviews, direct observation through field studies in selected areas as well as document analysis from authoritative sources such as official government documents and reports. The findings of the study conclude that there are two main challenges facing Malaysia in dealing with the issue of human trafficking, First, the enforcement aspect, mainly the coordination between the various responsible government agencies. Second, the delay in prosecution is an obstacle to the resolution of this issue from a legal perspective. Thus, this study found that it is very timely for the government to implement more proactive, effective measures continuous efforts to solve the crime of human trafficking in Malaysia.